Gum Arabic Edible Coating Reduces Postharvest Decay and Alleviates Nutritional Quality Deterioration of Ponkan Fruit During Cold Storage - Huang, Qiang; Wan, Chunpeng; Zhang, Yajie; Chen, Chuying; Chen, Jinyin (Frontiers in Nutrition, 2021)
The storability recession during storage limits postharvest storage life and nutritional value of Ponkan (Citrus reticulata Blanco) fruit which lead to huge losses. To develop an effective technique to reduce postharvest decay and maintain nutritional quality of Ponkan fruit, the preservation effect of postharvest gum arabic (GA) coatings at 9%, 12% and 15% was investigated on Ponkan fruit. The 12% and 15% GA coating effectively reduced fruit decay as well as weight loss, retained higher total soluble solid (TSS) content, suppressed titratable acidity (TA) degradation, and postponed the rise in ripening index (RI). Moreover, the 12% GA-coated fruit exhibited the lower respiration rate, electrical conductivity and malondialdehyde (MDA) accumulation than these in the uncoated (control) fruit. 12% GA coating treatment decreased the loss of ascorbic acid (AsA), total phenols and total flavonoids, and maintained higher non-enzymatic antioxidants amounts. Furthermore, 12% GA coating treatment increased antioxidant enzymes activities, as well as delayed the reduction of total antioxidant capacity (TAC). These results suggest that, with the cold storage increasing time, the 12% GA-coated fruit exhibited a better postharvest storability and higher nutritional quality than the control fruit. The GA coating treatment could be used as a commercial wax to improve postharvest storability, extend storage life and maintain nutritional value of Ponkan fruit up to 120 d of cold storage.